Варіанти у складі біблійних фразеологічних одиниць - Вергалюк, М. (Лексикографічний бюлетень, 2017)
In the proposed article we aim to distinguish phraseological variants of Bibleisms in lexicographic works of the Ukrainian language. Achievement of the set goal involves solving the following tasks: 1) to determine the place of the phenomenon of the variability of biblical phraseological units (hereinafter – BPU) among other systemic phenomena of the Ukrainian language; 2) to find out the essence and general features of the variant phraseological units (hereinafter - PU) of biblical origin; 3) to distinguish types of variants of the BPU in phraseological dictionaries of the Ukrainian language.